Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(C=\dfrac{5\cdot2^{12}\cdot3^8-3^9\cdot2^{12}}{2^{15}\cdot3^8-2^{13}\cdot3^9}\)
\(=\dfrac{2^{12}\cdot3^8\left(5-3\right)}{2^{13}\cdot3^8\left(2^2-3\right)}=\dfrac{1}{2}\cdot\dfrac{2}{1}=1\)
A = - 522 - { - 222 - [ - 122 - (100 - 522) + 2022] }
A = - 522 - { -222 - [- 122 - 100 + 522 ] + 2022}
A = - 522 - { -222 - { - 222 + 522 } + 2022}
A = - 522 - {- 222 + 222 - 522 + 2022}
A = -522 + 522 - 2022
A = - 2022
B = 1 + \(\dfrac{1}{2}\)(1 + 2) + \(\dfrac{1}{3}\).(1 + 2 + 3) + ... + \(\dfrac{1}{20}\).(1 + 2+ 3 + ... + 20)
B = 1+\(\dfrac{1}{2}\)\(\times\)(1+2)\(\times\)[(2-1):1+1]:2+ ... + \(\dfrac{1}{20}\)\(\times\) (20 + 1)\(\times\)[(20-1):1+1]:2
B = 1 + \(\dfrac{1}{2}\) \(\times\) 3 \(\times\) 2:2 + \(\dfrac{1}{3}\) \(\times\)4 \(\times\) 3 : 2+....+ \(\dfrac{1}{20}\) \(\times\)21 \(\times\) 20 : 2
B = 1 + \(\dfrac{3}{2}\) + \(\dfrac{4}{2}\) + ....+ \(\dfrac{21}{2}\)
B = \(\dfrac{2+3+4+...+21}{2}\)
B = \(\dfrac{\left(21+2\right)\left[\left(21-2\right):1+1\right]:2}{2}\)
B = \(\dfrac{23\times20:2}{2}\)
B = \(\dfrac{23\times10}{2}\)
B = 23
1, Đặt \(A=\frac{5.4^{15}.9^9-4.3^{20}.8^9}{5.2^9.6^{19}-7.2^{29}.27^6}\)
\(A=\frac{5.2^{30}.3^{18}-2^2.3^{20}.2^{27}}{5.2^9.2^{19}.3^{19}-7.2^{29}.3^{18}}\)\(A=\frac{2^{28}\left(5.2^2.3^{18}-2.3^{20}\right)}{2^{28}\left(5.3^{19}-7.2.3^{18}\right)}\)
\(A=\frac{5.2^2.3^{18}-2.3^{20}}{5.3^{19}-7.2.3^{18}}\)\(A=\frac{3^{18}\left(5.2^2-2.3^2\right)}{3^{18}\left(5.3-7.2\right)}\)
\(A=\frac{5.2^2-2.3^2}{5.3-7.2}\)\(A=2\)
\(\frac{9^3\cdot2^{10}\cdot27^5}{4^5\cdot81^6}=\frac{3^6\cdot2^{10}\cdot3^{15}}{2^{10}\cdot3^{24}}=\frac{1}{3^3}=\frac{1}{27}\)
\(\frac{27^4\cdot2^5-3^{11}\cdot4^3}{8^2\cdot9^6}=\frac{3^{12}\cdot2^5}{2^6\cdot3^{12}}-\frac{3^{11}\cdot2^6}{2^6\cdot3^{12}}=\frac{1}{2}-\frac{1}{3}=\frac{1}{6}\)
=))
a) \(\frac{9^3.2^{10}.27^5}{4^5.81^6}\)= \(\frac{\left(3^2\right)^3.2^{10}.\left(3^3\right)^5}{\left(2^2\right)^5.\left(3^4\right)^5}\)= \(\frac{3^{2.3}.2^{10}.3^{3.5}}{2^{2.5}.3^{4.5}}\)= \(\frac{3^6.2^{10}.3^{15}}{2^{10}.3^{20}}\)= \(\frac{3^{21}.2^{10}}{2^{10}.3^{20}}\)= \(\frac{3^{20}.2^{10}.3}{2^{10}.3^{20}}\)= \(3\)